Authentic voices : culturally responsive teaching and learning - Schmidt, Patricia Ruggiano, 1944- (Language, literacy, and learning., 2021)
"This book, authored by K-4 elementary educators, working at a publicly funded non-profit charter school, illustrates the power of culturally responsive teaching and learning as it becomes embedded in the New York State Education Curricu-lum. Educators, families, and community members contributed to this unique program with the goal of enhancing learning environments by applying the lan-guages and cultures of their students in their classrooms. Strong, carefully attentive, school leadership encouraged culturally responsive teaching and learning with the belief that children in this urban, economically stressed area could demonstrate significant academic and social/emotional gains. Readers of this book will witness culturally responsive lessons, family interviews, and whole school events that honor languages and cultures represented in the school. Sample classroom culturally responsive lessons tied to the curriculum, are presented. A montage of teachers, students, parents and community members will be created for readers to go online and witness culturally responsive teaching and learning (CRTL). Additionally, qualitative and quantitative student academic and affective gains are analyzed. Moreover, this book clearly demonstrates the talents, vision, and compassionate care given to children and their families by exceptional educators"--